Dystonia as complication of thalamic neurosurgery. (September 2019) - Picillo, Marina; Paramanandam, Vijayashankar; Morgante, Francesca; Algarni, Musleh; Olszewska, Diana A.; Munhoz, Renato Puppi; Aziz, Tipu; Pereira, Erlick; Hodaie, Mojgan; Kalia, Suneil K.; Lozano, Andres M.; Lynch, Tim; et al.
Abstract: Background: Thalamotomy and deep brain stimulation of the ventralis intermedius nucleus are effective symptomatic treatments for tremor, irrespective of the underlying diagnosis. Methods and results: Herein we describe six tremor patients (2 Parkinson's disease, 1 dystonic tremor, 2 Essential tremor plus dystonia, 1 Essential tremor plus ataxia) who underwent thalamic neurosurgery and acutely or sub-acutely developed dystonia that was permanent in three cases and could not be managed with any adjustments in the stimulation settings. Tremor response was excellent. We argue that thalamic procedures disrupted either or both the cerebello-thalamic and the cortico-striato-pallido-thalamo-cortical loop resulting in an increase of the thalamo-cortical outflow and subsequent change in the clinical picture from tremor to dystonia. Conclusion: Thalamic neurosurgery might be rarely complicated by dystonia. Why some patients are more prone to develop this adverse event is still unknown and possibly related to intrinsic factors, which certainly need further studies. Highlights: Six tremor patients developed dystonia after thalamic surgery. Thalamic surgery may disrupt the cerebello-thalamic or the cortico-striato-thalamo-cortical loop. Thalamic neurosurgery might be rarely complicated by dystonia.